Maternal environment alters dead pericarp biochemical properties of the desert annual plant Anastatica hierochuntica L. - Janardan Khadka; Buzi Raviv; Bupur Swetha; Rohith Grandhi; Jeevan R Singiri; Nurit Novoplansky; Yitzchak Gutterman; Ivan Galis; Zhenying Huang; Gideon Grafi (PLoS ONE)
The dead organs enclosing embryos (DOEEs) emerge as central components of the dispersal unit (DU) capable for long-term storage of active proteins and other substances that affect seed performance and fate. We studied the effect of maternal environment (salt and salt+heat) on progeny DU (dry indehiscent fruit) focusing on pericarp properties of Anastatica hierochuntica. Stressed plants displayed increased seed abortion and low level and rate of germination. Hydrated pericarps released antimicrobial factors and allelopathic substances that inhibit germination of heterologous species. Proteome analysis of dead pericarps revealed hundreds of proteins, among them nucleases, chitinases and proteins involved in reactive oxygen species detoxification and cell wall modification. Salt treatment altered the composition and level of proteins stored in the pericarp. We observed changes in protein profile released from seeds of salt-treated plants with a notable increase in a small anti-fungal protein, defensin. The levels of phytohormones including IAA, ABA and salicylic acid were reduced in dead pericarps of stressed plants. The data presented here highlighted the predominant effects of maternal environment on progeny DUs of the desert plant A. hierochuntica, particularly on pericarp properties, which in turn might affect seed performance and fate, soil fertility and consequently plant biodiversity.